تأثير التسميد والمسافات الزراعية على إنتاجية القرطم (Carthamus tinctorius L.) من البتلات والبذور والزيت - عبد العزيز, محمد; سليمان, علي اسكندر; لانغر, بيتر; درويش, راما (Latakia University Journal -Biological Sciences Series, 2014)
نفذ البحث خلال الفترة 2011 و2012 بهدف دراسة تأثير 5مستويات من التسميد (المعدنيN65:P65:K70 كغ/ﮪ، والعضوي 5، 10، 15 طن/ﮪ)، وثلاث مسافات زراعية بين الخطوط هي (50 – 75 – 100) سم، والمسافة بين النبات والآخر على الخط الواحد 15 سم والتفاعل بينهما على إنتاجية القرطم من البتلات والبذور والزيت بينت الدراسة النتائج الآتية: تفوقت معنوياً كافة معدلات التسميد المدروسة على الشاهد في الإنتاج من البتلات الجافة والإنتاج من البذور والزيت، بينما لم يكن هناك فروق معنوية في متوسط نسبة الزيت بين مختلف معاملات التسميد والشاهد . سببت مسافة الزراعة 100 سم بين الخطوط تفوقاً معنوياً في متوسط الإنتاج من البذور، بينما تفوقت المسافة 50 سم بين الخطوط في متوسط الإنتاج من البتلات الجافة، ولم يظهر تأثير لأبعاد الزراعة على نسبة الزيت في البذور وانخفض متوسط الإنتاج من الزيت بالهكتار مع ازدياد مسافة الزراعة بين خطوط الزراعة من 100 سم إلى 75سم و 50سم . أعطى التفاعل بين معدلات التسميد المدروسة ومسافات الزراعة تأثيراً معنوياً في أغلب الصفات المدروسة وبلغ أكبر تأثير معنوي للتفاعل بين التسميد المعدني والمسافة 100 سم، ثم معدل التسميد العضوي 15 طن/ﮪ والمسافة 100 سم. The research was carried out during 2011-2012 in order to study the effects of five levels of fertilization (mineral fertilization N:65 P:65 K:70kg/h, and organic fertilization 5, 10 and 15ton/h), three spaces between rows (50, 75, and 100cm), one 15cm space between one plant and another, and the interaction between them on the production of safflower dry colored leavel, seed, and oil. The study showed the following results: all the levels of the studied fertilization were significantly superior in the production of dry colored leavel, seed and oil over the control. However, there were no positive differences in the proportion of oil between the treatments of fertilization and the control. The 100cm farming space among rows led to a significant positive effect in the production of safflower seeds, while the 50cm distance among farming rows in the production of dry coloring leaves was superior over 100cm and 75cm distance. There were no positive differences in the proportion of oil; while the mean of oil productivity came down whenever the plant spacing increased from 50 to 75 and then 100cm. The interaction between the levels of the studied fertilization and agricultural plant spaces gave a positive significant effect in most studied characteristics. The most significant positive effect was for the interaction between the mineral fertilization and 100cm distance, and then came the average of the organic fertilization 15ton/h and 100cm space between rows.